Sedimentary characteristics and depositional models of two types of homogenites in an Eocene continental lake basin, Shulu Sag, eastern China. (1st August 2019) - Kong, Xiangxin; Jiang, Zaixing; Han, Chao; Li, Haipeng; Li, Qing; Zheng, Lijing; Yang, Yepeng; Zhang, Jianguo; Xiao, Fei
Graphical abstract: Highlights: Two types of homogenites are found in the Shulu Sag based on sedimentary characteristics. Earthquakes are the most reasonable triggers of homogenite formation. Seismic shaking and basin morphology control the formation of homogenites. Abstract: Homogenites are homogeneous and structureless, fine-grained rocks. They have been studied extensively in marine settings and are typically interpreted as being related to catastrophic events such as earthquakes. However, studies on lacustrine homogenite-like rocks are limited. New core data from the Shulu Sag in China reveal that thick massive calcilutites exist in the lower Shahejie 3 Formation, which formed during the middle Eocene rifting stage. Based on petrographic, geochemical, and mineralogical data, these massive calcilutites are interpreted as homogenites and grouped into two types. Type A homogenite is composed of intrabasinal materials characterized by high calcite, total organic carbon (TOC) content, and δ 13 C value. Type A homogenite has two facies successions, the first of which is characterized by homogeneous appearance capped by an erosional interface and the second is characterized by repeated massive-laminated calcilutite successions. Type B homogenite contains abundant allochthonous materials displaying relatively high dolomite content and low calcite, TOC, and δ 13 C content. Type B homogenite represents the topmost finer portion of a graded megabed which includes, from base to top, grain supported carbonate conglomerates, slumped deformed portions, and debrites. The whole unit can be considered as a megaturbidite. Earthquakes are the most reasonable triggers of homogenite formation in the Shulu Sag. Type A homogenites are thought to be derived by fluidification, resuspension, and decantation of lacustrine fines due to shock waves generated by an earthquake. Type B homogenites might be deposits of distal turbidity currents and turbid clouds transformed from other gravity flows. The results of this study provide a better understanding of the formation of homogenites caused by earthquakes in a confined lacustrine basin.